2000
DOI: 10.1002/1529-0131(200012)43:12<2722::aid-anr12>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Restricted VH3 gene usage in phage-displayed Fab that are selected by intravenous immunoglobulin

Abstract: Objective T o perform a comparative analysis of 1) intravenous Ig (IVIG)–bound Fab fragments from a patient with autoimmune thrombocytopenia that had progressed to systemic lupus erythematosus (SLE) and 2) IVIG‐selected Fabs from an SLE patient without thrombocytopenia. Methods IVIG preparations have been successfully used to treat certain cases of autoimmune thrombocytopenia and SLE. Specific interactions of IVIG with the components of the immune system are not well characterized. To investigate these, we had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…As there are approximately 50 different functional VH fragments in the human genome that can potentially be used, 12,13 the selective usage of the VH fragments detected in Group A tumors strongly suggests that these tumors may be derived from highly restricted B cell subsets. VH3-23 and VH3-30 have been closely associated with autoimmune disease, with the former found in patients with autoimmune thrombocytopenia, 28,29 Graves' disease, 30 and Wegener's granulomatosis, 31 and the latter in patients with systemic lupus erythematosus, 29 autoimmune thrombocytopenia, 28 and Kawasaki's disease. 32 In contrast, a biased usage of particular VH fragments has been reported in chronic lymphoid leukemia (VH3-21), 14,15 splenic marginal zone lymphoma (VH1-2), 16 and salivary MALT lymphoma (VH1-69).…”
Section: Discussionmentioning
confidence: 99%
“…As there are approximately 50 different functional VH fragments in the human genome that can potentially be used, 12,13 the selective usage of the VH fragments detected in Group A tumors strongly suggests that these tumors may be derived from highly restricted B cell subsets. VH3-23 and VH3-30 have been closely associated with autoimmune disease, with the former found in patients with autoimmune thrombocytopenia, 28,29 Graves' disease, 30 and Wegener's granulomatosis, 31 and the latter in patients with systemic lupus erythematosus, 29 autoimmune thrombocytopenia, 28 and Kawasaki's disease. 32 In contrast, a biased usage of particular VH fragments has been reported in chronic lymphoid leukemia (VH3-21), 14,15 splenic marginal zone lymphoma (VH1-2), 16 and salivary MALT lymphoma (VH1-69).…”
Section: Discussionmentioning
confidence: 99%
“…However, biases in gene family usage of the heavy-chain variable region have been reported in a number of diseases. For example, restricted VH3 germ line gene usage was observed in intravenous immunoglobulin-bound Fabs from a patient with thrombocytopenia that had progressed to systemic lupus erythematosus (31). It is known that VH3 antibodies are also important for defense against a variety of bacteria (1,39,40) and viruses (2,17,20).…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing of IVIg-binding antibodies in a small number of patients with autoimmune disorders has suggested that IVIg can act in a manner analogous to a B-cell superantigen 15 and that B cells using V H 3Á23 and V H 3Á30/3Á35 are selectively activated following IVIg therapy. 16 Dimers and higher-order aggregates of IgG in IVIg preparations have been shown to activate neutrophils via triggering of macrophages.…”
Section: Activation Of Specific Cellsmentioning
confidence: 99%